Digital Marketing for Knitted Bag With Japan as an Export Target: Case Study of Crochetwoven - Amalia, Ishica Azzahra; Khoirotunnisa, Fani (CV. Lenggogeni Data Publishing, 2023)
This research delves into the digital marketing strategies employed by CrochetWoven, a brand specializing in woven bags, as it expands its presence in the Japanese market for export purposes. The primary goal of this study is to comprehend how digital marketing and the internet serve as effective tools to reach international markets, particularly in consumer industries like woven bags.The research methodology involves gathering and analyzing various literature, references, and marketing journals from diverse sources, ranging from conventional books to relevant E-books that align with the discussed theories. Emphasizing social media and e-commerce, the study presents a case analysis of how CrochetWoven successfully broadened its market share by leveraging prominent e-commerce platforms in Japan, such as Amazon Japan, Rakuten, and Rakuma. The findings highlight significant potential for CrochetWoven to expand its digital marketing through e-commerce utilization, with a deep understanding of consumer behavior in Japan being a crucial factor for the company's success in entering and thriving in the export market.